Telerehabilitation During the Covid-19 Pandemic in Outpatient Rehabilitation Settings: A Descriptive Study - Werneke, Mark W (Phys Ther, 2021)
OBJECTIVE: COVID-19 has widely affected delivery of health care. In response, telerehabilitation (TR) has emerged as alternative care model. Aims were: (1) describe baseline patient characteristics and available unadjusted outcomes for episodes of care administered during COVID-19 using TR vs. traditional in-person care, (2) describe TR frequency levels by condition and telecommunication modes. METHODS: A descriptive retrospective observational design was used to report patient variables and outcomes including physical function, number of visits, and patient satisfaction, by TR frequency (few, most, or all visits) and telecommunication modes. Standardized differences were used to compare baseline characteristics between episodes with and without TR. RESULTS: Sample consisted of 222,680 patients [59% female; mean age (SD) = 55(18)]. Overall TR rate was 6% decreasing from 10% to 5% between 2(nd) and 3(rd) quarters of 2020. Outcome measures were available for 90% to 100% of episodes. Thirty-seven percent of clinicians administered care via TR. Patients treated using TR compared to in-person care were more likely to be younger, and live in large metropolitan areas. From those with TR, 55%, 20%, and 25% had TR during few, most, or all visits, respectively. TR care was administered equally across orthopedic body parts, with lower use for non-orthopedic conditions such as stroke, edema, and vestibular dysfunction. TR was primarily administered using synchronous (video or audio) modes. The rate of patients reported being very satisfied with their treatment results was 3% higher for no TR compared to TR. CONCLUSIONS: These results provide new knowledge about to whom and how TR is being administered during the pandemic in outpatient rehabilitation practices throughout the USA. The database assessed was found to be suitable for conducting studies on associations between TR and diverse outcome measures, controlling for a comprehensive set of patient characteristics, to advance best TR care models, and promote high quality care. IMPACT: This study provided detailed and robust descriptive information using an existing national patient database containing patient health and demographic characteristics, outcome measures, and TR administration data. Findings support the feasibility to conduct future studies on associations between TR care and patient outcomes, adjusting for a wide range of patient characteristics and clinical setting factors that may be associated with the probability of receiving TR. Finding of limited and decreasing use of TR over the study period calls for studies aimed to better understand facilitators and inhibitors of TR use by rehabilitation therapists during everyday practice to promote its use when clinically appropriate.